A small speech community with many small languages: The role of receptive multilingualism in supporting linguistic diversity at Warruwi Community (Australia). (September 2018) - Singer, Ruth
Abstract: At Warruwi Community (pop. 400), nine very different Indigenous languages are still widely used, which is unusual in the contemporary Australian Indigenous context. Using the receptive multilingual mode, speakers frequently address one another in different languages. This mode offers speakers of small languages such as Mawng (ca. 400 speakers) an alternative to accommodating to larger languages such as Yolngu-matha (ca. 2000 speakers). Although not unique to Warruwi, receptive multilingual practices are part of a set of "mutually constituting ideologies and practices" (Nakassis, 2016) that co-construct a speech community where many small languages flourish. Highlights: Using the receptive multilingual mode, people at Warruwi often address one other in different languages. Local perspectives on diversity support this lack of accommodation, assumed to be universal in multilingual interactions. Warruwi constitutes a speech community because people draw on shared interpretations of indexicality. Mutually constituting language ideologies and practices allow many small languages to flourish at Warruwi.